Estructura y composición florística de un bosque siempreverde montano bajo en un gradiente altitudinal en la parroquia San Francisco del vergel, cantón Palanda, provincia de Zamora Chinchipe - Rosales Guayanay, Jilson Damian (2022)
Knowledge of floristic resources is important to plan their management and conservation. The objective of this research is to determine the structure and floristic composition of the lower montane evergreen forest considering the altitudinal gradient in the parish of San Francisco del Vergel, Palanda, Zamora Chinchipe. 18 temporary plots of 20 mx 20 m (400 m2) were installed for trees, within each plot of 400 m2 three subplots of 5 mx 5 m (25 m2) were nested for the shrub layer and five subplots of 1 mx 1 m ( 1 m2) for the herbaceous layer. All individuals greater than 5 cm D1.30 m were measured. The floristic composition was determined and the structural parameters were calculated. 152 species belonging to 111 genera and 65 families were recorded, of which 117 are trees, 18 shrubs and 17 herbs, with a total of 840 individuals greater than 5 cm DBH. The most diverse families of the tree stratum are: Myristicaceae, Rubiaceae and Lauraceae; from the shrub layer: Annonaceae, Poaceae and Solanaceae; and in the herbaceous stratum Ciperaceae, Polypodiaceae and Araceae. The ecologically important species of the tree stratum are: Nectandra reticulata and Otoba glycycarpa, in the shrub stratum: Oreopanax sp., Rollinia andicola and Solanum sp.; and Anthurium sp., in the herbaceous stratum. The vertical structure of the forest presents three strata: dominant, co-dominant and dominated, existence of clearings in the forest. The largest number of individuals are concentrated in diameter classes I and II, reflecting an inverted "J" shaped structure, characteristic of forests in recovery. The floristic composition of the lower montane evergreen forest of the San Francisco del Vergel parish is not largely affected by the altitudinal gradient, with the same plant species found in each gradient Keywords: Low montane evergreen forest, San Francisco del Vergel, floristic composition, diametric structure, structural profiles.